2003
DOI: 10.1142/s0192415x03001600
|View full text |Cite
|
Sign up to set email alerts
|

Study of Sokei-Kakketu-To (Shu-Jing-Huo-Xue-Tang) in Adjuvant Arthritis Rats

Abstract: To examine the effectiveness of the herbal medicine prescription, Shu-Jing-Huo-Xue-Tang (SJHXT), for pain relief, we performed a study using rats with adjuvant arthritis (AA). After injecting the adjuvant, AA rats were maintained for 6 months as a chronic pain model. Starting at 6 months, SJHXT was administered for 12 weeks. We measured the tail skin temperature and locomotor activity of rats using thermography and a metabolism measuring system, respectively, before and after 12 weeks of SJHXT administration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The reason causing this phenomenon is unclear. However, as we described above, although the primary active analgesic herbal component is Shaoyao which producing the analgesic effect on CCI rats through activating alpha-2 adrenoceptors, other herbal components in SJHXT may enhance or augment the effect of Shaoyao (Kanai et al, 2003;Borchers et al, 2000). Thereby, if exhibiting the same analgesic potency, SJHXT may activate fewer alpha-2 adrenoceptors than clonidine and then the central side effects of SJHXT such as sedation and hypotension are less than clonidine.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The reason causing this phenomenon is unclear. However, as we described above, although the primary active analgesic herbal component is Shaoyao which producing the analgesic effect on CCI rats through activating alpha-2 adrenoceptors, other herbal components in SJHXT may enhance or augment the effect of Shaoyao (Kanai et al, 2003;Borchers et al, 2000). Thereby, if exhibiting the same analgesic potency, SJHXT may activate fewer alpha-2 adrenoceptors than clonidine and then the central side effects of SJHXT such as sedation and hypotension are less than clonidine.…”
Section: Discussionmentioning
confidence: 94%
“…Third, the analgesic effect of Paeoniflorin, the main ingredient of Shaoyao, on neonatal maternal separation-induced visceral hyperalgesia in rats is mediated by kappa-opioid receptors and alpha-2 adrenoceptors in the central nervous system (Zhang et al, 2008). Fourth, SJHXT includes several analgesic herbal components other than Shaoyao and also includes several herbal components to improve tissue perfusion and to modulate immune response (Kanai et al, 2003;Borchers et al, 2000). Fifth, it is well known that herbal medicine which is a combination prescription has unique synergistic and synthetic effects, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Shu-Jing-Huo-XieTang has been frequently investigated in Taiwan (Hsieh et al, 2008) and was determined to be most commonly used herbal formula for treating "diseases of the musculoskeletal system and connective tissue" in climacteric women (Yang et al, 2009). One study reported that this formula exerted pain relieving effects by increasing blood circulation in the adjuvant arthritis rat models (Kanai et al, 2003). Although TCM physicians frequently prescribe this formula in clinical practice in Taiwan, a previous study has revealed that a combination of Shu-Jing-Huo-Xie-Tang and warfarin will enhance bleeding effects in animal models .…”
Section: Discussionmentioning
confidence: 99%
“…It had been proved to have effects in treating musculoskeletal disease and connective tissue [44], and had effects of pain relief with the mechanism of increasing blood circulation in the adjuvant arthritis rats model [45]. The third common Chinese herbal formula was “Dang-gui-nian-tung-tang”, it had been shown to have anti-inflammation and immune regulation effects on experimental OA rats [46].…”
Section: Discussionmentioning
confidence: 99%